Nanoparticle-based mobile biosensors for the rapid detection of sepsis biomarkers in whole blood. Issue 3 (24th February 2020) - Alba-Patiño, Alejandra; Russell, Steven M.; Borges, Marcio; Pazos-Pérez, Nicolás; Álvarez-Puebla, Ramón A.; de la Rica, Roberto
Abstract : Detecting small variations in the levels of IL-6 is crucial for the early diagnosis of sepsis. Abstract : Detecting small variations in the levels of IL-6 is crucial for the early diagnosis of sepsis. To be useful in clinical decision-making, this requires detecting IL-6 rapidly in whole blood and with portable readers. Here we introduce immunosensors made of filter paper that use plasmonic nanoprobes to detect IL-6 rapidly in unprocessed blood with an unmodified smartphone. Key aspects of the biosensor fabrication were optimized in order to reduce the assay time without losing sensitivity. This included testing three bioconjugation routes for protein attachment to nanoprobes using gold nanoparticles covered with carboxylate or amine moieties, or polyvinylpyrrolidone (PVP), as starting materials, and using alternating layers of polyelectrolytes to bind the capture antibody to the paper substrate. Smartphone-based signal quantification was achieved with a custom-made app featuring a unique augmented reality guidance system that circumvents the need for smartphone attachments and automates all the steps involved in color quantification. The biosensors were able to detect IL-6 with a limit of detection of 0.1 pg mL −1 and a total assay time within 17 min. They could also detect an increase in IL-6 of only 12.5 pg mL −1 over basal levels in whole blood with 99% confidence. The high sensitivity and rapid turnaround time afforded by the optimized biosensors and the fully automated real-time densitometry app make our biosensors well suited for emergency healthcare situations such as the identification of potential sepsis cases.